Light and life - Gross, Michael, 1963- (Oxford University Press, 2002)
There would be no life on Earth without light from the Sun, and life would not be as highly evolved as it is had it not made the best use of light's energy and information for using photosynthesis, biological clocks, and vision. In Light and Life, Michael Gross explores six major aspects of the complex and fascinating interplay between light and life, ranging from the mythical role of the Sun in ancient cultures to the latest advances in scientific research, covering photosynthesis, bioluminescence, vision, perception, and biological clocks. - ;Light, like no other physical phenomenon, is linked in a wide variety of ways with the biological phenomenon of life. We can read this page because light is reflected from it, and carries the information to the retina; the oxygen we breathe was produced by photosynthesis; our sense of alertness relies on our biological clock, set using the cues of light and dark. Michael Gross explores the symbiotic relationship of light and life in this intriguing and entertaining book. Starting with astronomy and our relationship with the Sun and dependence on photosynthesis, he then turns to some of the stranger outcomes of the relationship - bioluminescent creatures, and their evolutionary significance. Finally he looks at the influence of light on biological time-keeping, the focus of much current scientific research. Life would not be here without light, and it would not have evolved as it has done had it not made the best possible use of light's energy and information content for using photosynthesis, biological clocks, and vision. This book explores all these aspects of the fascinating interplay of these two phenomena in a lively manner using many intriguing examples.